2016
DOI: 10.31298/sl.140.11-12.6
|View full text |Cite
|
Sign up to set email alerts
|

Forestry work-related injuries in Forest estate „Sremska Mitrovica“ in Serbia

Abstract: Šumarstvo je jedna od gospodarskih grana gdje je stopa ozljeda na radu među najvećima. Uprkos tomu što se poslovi u šumarstvu uglavnom karakteriziraju sezonalnošću, a ne stalnom zaposlenošću radnika, šumsko gospodarstvo „Sremska Mitrovica“ gdje su provedena istraživanja ima drukčiju praksu. Cjelokupna sječa i izrada na području ovoga gospodarstva obavlјa se ulaganjem vlastitih sredstava i vlastite radne snage. Ovo gospodarstvo karakterizira ravničarski teren s prosječnim nadmorskim visinama ispod 100 m, gdje g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 3 publications
1
5
0
Order By: Relevance
“…Picchio et al [7] and Halilović et al [33] found that the most common was damage ranging in sizes of 25-100 cm 2 ; Tavankar et al [6] found it to be 101-200 cm 2, and Tavankar and Bodaghi [27] found <10 cm 2 . The range of damage size (4.71-2486.88 cm 2 ) was similar to 4-2000 cm 2 as found by Sabo [80], smaller than 28-5250 cm 2 as found by Sabo [81], and higher than 12-600 cm 2 as found by Danilović et al [41].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Picchio et al [7] and Halilović et al [33] found that the most common was damage ranging in sizes of 25-100 cm 2 ; Tavankar et al [6] found it to be 101-200 cm 2, and Tavankar and Bodaghi [27] found <10 cm 2 . The range of damage size (4.71-2486.88 cm 2 ) was similar to 4-2000 cm 2 as found by Sabo [80], smaller than 28-5250 cm 2 as found by Sabo [81], and higher than 12-600 cm 2 as found by Danilović et al [41].…”
Section: Discussionsupporting
confidence: 86%
“…The average size of the damage was 197.08 cm 2 , which is smaller than the 610 cm 2 found by Tsioras and Liamas [79], 608 cm 2 found by Sabo [81], 460.35 and 262.40 cm 2 found by Nikooy et al [25], and 228.29 cm 2 found by Sabo [80]; and higher than the 65.16 and 81.66 cm 2 found by Gurda et al [39], 92.26 cm 2 found by Halilović et al [33], 145.32 cm 2 found by Dudáková et al [8], 165.7 cm 2 found by Tavankar and Bonyad [31], and 145.4 and 176.6 cm 2 found by Danilović et al [41]. The most common was damage ranging in sizes of 50-200 cm 2 (45.45%), which was confirmed by Danilović et al [41] and Tsioras and Liamas [79] for one site with a share of 40.4%, while on the other three sites, damage of sizes >200 cm 2 were the most common. Picchio et al [7] and Halilović et al [33] found that the most common was damage ranging in sizes of 25-100 cm 2 ; Tavankar et al [6] found it to be 101-200 cm 2, and Tavankar and Bodaghi [27] found <10 cm 2 .…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…The forestry sector is one of the industries of the national economy with the highest injury risk. The specific working conditions in forests, involving the type of terrain, weather conditions, and the use of power tools and heavy machinery, make work hazardous, with a certain risk of serious injuries [1,2,3,4]. The risk of work-related injuries is very high in forestry jobs in general [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The high consequent risk through exposure to occupational hazards has informed the ergonomic improvement interventions worldwide (Ohlander et al, 2020). In countries, where data are available, forestry has consistently over the years been considered as one of the most hazardous occupations around the world (FAO, 1992;ILO, 1998;Klun and Medved, 2007;Ozden et al, 2011;Melemez, 2015;Danilovic et al, 2016;Grzywinski et al, 2016;HSE, 2021). While the sustenance of quality of labour, in particular, those in forest-based industries has become one of the major global concerns, most studies mainly focused on forest personnel, logging and primary conversion operations (Mitchell et al, 2008;Balimunsi et al, 2011;Tripathi and Upadhyay, 2015;Yovi and Yamada, 2019).…”
mentioning
confidence: 99%